DESAIN MARKETING INFORMATION SYSTEMS PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI DESA TAMAN SARI KABUPATEN BANYUWANGI - A.A Gde Satia Utama; Izzato Millati (UNEJ e-Proceeding)
Desa Taman Sari in Banyuwangi has a tremendous potential in the development of SMEs processed products. However, SMEs in this village are not optimal, especially from the aspect of marketing their products. They need strategies in the marketing of SME products in competitive era. Information technology plays an important role in marketing products of SMEs. The purpose of this study are to design system based on marketing information online. This study uses the exploratory method. Model design using flowcharts, diagram context, and entity relationship diagrams. Stages of analysis carried out by the flow of input, process and output. The results of the marketing information system design can manage sales reports, product, pricing, and marketing strategies of SME products, and the competitive advantage of SMEs can be achieved.